Risk of pediatric inflammatory multi-system syndrome (PIMS or MIS-C) in pediatric patients with COVID-19 presenting with gastrointestinal symptoms - Jaramillo-Esparza, Carlos Mauricio; Vázquez-Frias, Rodrigo (Frontiers in Pediatrics, 2022)
Introduction and objectives: Pediatric inflammatory multisystem syndrome (PIMS) is a life-threatening complication in pediatric patients with SARS-CoV-2 infection. An increase in the association of gastrointestinal symptoms and the presence of PIMS has been observed. The objective of this study was to analyze whether pediatric patients with COVID-19, who debut with gastrointestinal symptoms, have a higher risk of developing PIMS. Material and methods: An observational, analytical and retrolective study was carried out with a review of the records of patients diagnosed with COVID-19. Demographic, clinical and laboratory variables were recorded. Results: A total of 248 patients who met the selection criteria were included. Of Those 40% were female, with a mean age of 7 +/- 5.8 years. Gastrointestinal symptoms were the initial presentation in 103 patients, with vomiting being the most frequent symptom, followed by abdominal pain and diarrhea. In total 52 patients developed PIMS, 30 of whom presented with gastrointestinal symptoms. A RR of 1.57 (97% CI of 1.17-2.11) was found for the presentation of PIMS in patients positive for SARS-CoV 2 who present with gastrointestinal symptoms. Conclusions: There is an increased risk of developing pediatric multisystem inflammatory syndrome when there are gastrointestinal symptoms in pediatric patients with COVID-19.